2014
DOI: 10.3791/51195
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Blood-vessel-derived Multipotent Precursors from Human Skeletal Muscle

Abstract: Since the discovery of mesenchymal stem/stromal cells (MSCs), the native identity and localization of MSCs have been obscured by their retrospective isolation in culture. Recently, using fluorescence-activated cell sorting (FACS), we and other researchers prospectively identified and purified three subpopulations of multipotent precursor cells associated with the vasculature of human skeletal muscle. These three cell populations: myogenic endothelial cells (MECs), pericytes (PCs), and adventitial cells (ACs), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 30 publications
1
23
0
Order By: Relevance
“…This view could explain the establishment of MSC cultures by AT3G5Cs as shown here and by CD146 + CD56 -perivascular cells in various organs [8], including skeletal muscle [44].…”
Section: Studies In Which 3g5supporting
confidence: 55%
“…This view could explain the establishment of MSC cultures by AT3G5Cs as shown here and by CD146 + CD56 -perivascular cells in various organs [8], including skeletal muscle [44].…”
Section: Studies In Which 3g5supporting
confidence: 55%
“…As previously mentioned, MSCs are self-renewing multipotent stem cells that can differentiate into cells of the musculoskeletal system and secrete paracrine factors to promote tissue regeneration [ 3 5 , 8 11 , 13 , 14 , 16 20 , 22 , 24 , 26 28 , 30 , 37 39 ]. While their origin is still subject to ongoing investigations, some studies have indicated that MSCs are derived from pericyte-like cells [ 3 , 40 ] and are associated with blood vessels throughout the body in tissues such as muscle [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…As previously mentioned, MSCs are self-renewing multipotent stem cells that can differentiate into cells of the musculoskeletal system and secrete paracrine factors to promote tissue regeneration [ 3 5 , 8 11 , 13 , 14 , 16 20 , 22 , 24 , 26 28 , 30 , 37 39 ]. While their origin is still subject to ongoing investigations, some studies have indicated that MSCs are derived from pericyte-like cells [ 3 , 40 ] and are associated with blood vessels throughout the body in tissues such as muscle [ 5 ]. As a result, these cells can be isolated from multiple tissues including adipose[ 27 ], amniotic fluid [ 13 ], bone marrow [ 10 , 20 ], cord blood [ 9 ], teeth [ 18 ], heart [ 4 ], neuroglia [ 16 ], placenta [ 14 ], synovium [ 8 ], skeletal muscle [ 5 , 26 ] as well as skin [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the cell surface marker expression identified by immunohistochemistry, we discovered a unique combination of surface antigens for each subset of hBVSCs that allows one to purify these cells to homogeneity through FACS: MECs (CD34+/56+/144+/45−), PCs (CD146+/34−/45−/56−), and ACs (CD34+/31−/45−/56−/146−) [ 16 , 18 , 28 ]. The isolation and purification of hBVSC subpopulations have been well established [ 46 ]. The workflow of hBVSC purification from fresh human skeletal muscle biopsy is illustrated in Figure 1 .…”
Section: Purification Of Human Blood-vessel-derived Stem Cellsmentioning
confidence: 99%